Računalniško podprto konstruiranje cestne varnostne ograje - Vesenjak, Matej (Strojniški vestnik, 2003)
Road restraint barriers on public roads are used to prevent a vehicle from veering off the road or breaking through on to the opposite carriageway. The European standard SIST EN 1317 specifies the criteria that the road restraint barrier has to meet during testing. Practical observations have shown that thedistance spacer currently used in the road restraint barriers in Slovenia is too stiff. This results in too rapid decelerations during vehicle impact. Designing an improved distance spacer is therefore extremely important for increasing the safety of vehicle occupants. The purpose of this research was to design a new distance spacer that deforms in a controllable manner and has an increased capacity for strain-energy absorption during vehicle impact. The new designs were analyzed with the finite-element method. In the initial phaseof the research, the stiffness of various designs of distance spacer was analyzed using quasi-static elastic-plastic analyses of a three-dimensional road-restraint-barrier model. It was found that the currently used distance spacer is indeed much too stiff and that new distance-spacer designs are capable of larger, controllable elastic-plastic deformation during vehicle impact.
Keywords: varnost na cestah; ograje varnostne; konstruiranje; simuliranje numerično; simuliranje nelinearno; varnostne ograje; simulacija